A Cross-Sectional Study of Chronic Impairments and Activity Limitations in Women at Least Six Months Post-Operative for Breast Cancer: An Exploratory Study. - Wong, Vicki (Université d'Ottawa / University of Ottawa, 2014)
Objective: The increased survival rate amongst female breast cancer survivors creates a need for an understanding of chronic disability after surgery. The objective of this study is to explore the association between impairments (e.g., pain, mobility, strength) and the personality trait, fear of physical activity, and chronic daily activity limitations for women who had their surgery at least six months prior to the study. Hypothesis: The study hypothesis is that women with high levels of physical impairments and the personality trait of fear of physical activity will also have higher levels of daily activity limitations six months or more after their breast cancer surgery. Design: A cross-sectional design. Outcome Measures: Disabilities of Shoulder, Arm, and Hand (DASH), Visual Analog Scale for Pain (VAS-Pain), Fear Avoidance Belief Questionnaire – Physical Activity (FABQ-PA), and objective measures of shoulder mobility and strength. Participants: Women who had been diagnosed and undergone surgery for breast cancer, stage 1-3. They must have had their surgery at least six months previously and have completed chemotherapy or radiation therapy. Both English- and French-speaking women from the Ottawa-Gatineau region were eligible. Results: Data from twelve women were analysed with a mean age of 58.0±8.9 years and post-operative time of 4.0± 2.8 years. DASH scores mean was 12.2 ± 11.38. VAS-Pain (rs=0.819; p<.001), FABQ-Physical Activity (rs=0.746; p<.005) were significantly associated with DASH score, whereas non-significant associations were found with supraspinatus strength (rs = 0.182; p < .572) or infraspinatus strength (rs=0.553; p<.062) using the Spearman Rho test. Also, no significant relationships were observed between range of motion (hand-behind-back; p =.366; hand-behind-head; p=.390) and DASH scores using a Kruskal-Wallis test. Conclusion: The results of this exploratory study suggest that the reported daily activity limitations of women who have had breast cancer surgery may be related to the participant pain perception and/or fear of physical activity.
Keywords: Breast Cancer; Chronic Activity Limitations; Disability; Fear of activity